PENGARUH VARIASI KONSENTRASI AMILUM Zea mays (L) SEBAGAI BAHAN PENGHANCUR SECARA GRANULASI BASAH TERHADAP SIFAT FISIK TABLET PARASETAMOL - Dewi rashati, Amirul Fauziah (AKADEMI FARMASI JEMBER, 2017)
This research is aims to determine the effect of variation concentration starch Zea mays (L) as disintegration agent in wet granulation to physical characteristics paracetamo. This research used eperimental method by one shot case study. Paracetamol as active ingredient, starch zea mays (L)as desintegrant agent, PVPK30 as binding agent, avicel as filler and Mg stearat as lubricants. The result of SPSS showed significant (p0,05), that means no difference in the three formulation. The first test is weight uniformity show that from column A and B qualify weight requirement range, hardness test. Showed significant (p0,05) that means nodifference in the three formulation. Friability test showed significant (p 0,05) the last is disintegration time test showed that significant (P0,05) no difference in the three formulation. The research of physic characteristic of the tablet showed that hardness test and time test not qualif. Analysis SPSS showed (p0,05) no difference in the three formulation and amilum had no effect on physical test of paracetamol tablet.Keywords: zea mays (L),paracetamol,physicial characteristic